The current state of the research and future perspectives for the methodology and the interpretation of Byzantine pottery of the 11th and 12th centuries AD - Yangaki, Anastasia G. (Journal of Greek Archaeology, 2016)
Even though researchers became interested in the study of Middle Byzantine ceramics at a very early stage, in the first decades of the 20th century, it’s only during the past two decades and especially since the beginning of the 21st century that we can observe a more systematic research. Its point of focus is located in the renewed typological classification of some pottery categories; in clarifying issues of dating and provenance; and in dealing with the coarse, usually undecorated pottery, the cooking wares and the transport and storage vessels. Up until then (and in some cases even now) research gave special emphasis on the study of fine glazed pottery.